2017
DOI: 10.1371/journal.pone.0181617
|View full text |Cite
|
Sign up to set email alerts
|

Understanding spearfishing in a coral reef fishery: Fishers’ opportunities, constraints, and decision-making

Abstract: Social and ecological systems come together during the act of fishing. However, we often lack a deep understanding of the fishing process, despite its importance for understanding and managing fisheries. A quantitative, mechanistic understanding of the opportunities fishers encounter, the constraints they face, and how they make decisions within the context of opportunities and constraints will enhance the design of fisheries management strategies to meet linked ecological and social objectives and will improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…it is a way to monitor and assess the activity, to educate about some yet unacquired responsible fishing habits, and to modify contests minimum weight for some species with a big divergence between MLL and MSaL. deconstructing the process of fishing from the fishers' perspective can help fisheries researchers understand social-ecological interactions and identify leverage points for management (Pavlowich and Kapuscinski 2017). in Lloret et al (2016), it is concluded that it is necessary to integrate different assessment approaches (biological, social and economic), with active participation from stakeholders, governments and relevant research institutions, to better evaluate and manage coastal fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…it is a way to monitor and assess the activity, to educate about some yet unacquired responsible fishing habits, and to modify contests minimum weight for some species with a big divergence between MLL and MSaL. deconstructing the process of fishing from the fishers' perspective can help fisheries researchers understand social-ecological interactions and identify leverage points for management (Pavlowich and Kapuscinski 2017). in Lloret et al (2016), it is concluded that it is necessary to integrate different assessment approaches (biological, social and economic), with active participation from stakeholders, governments and relevant research institutions, to better evaluate and manage coastal fisheries.…”
Section: Discussionmentioning
confidence: 99%
“…We modeled the population dynamics of a single parrotfish species with high ecological and fishery value in the Caribbean: stoplight parrotfish, Sparisoma viride. In addition to its importance, this fish is well studied (Cardwell and Liley, 1991;Koltes, 1993;J Bruggemann et al, 1994;van Rooij et al, 1995;1996b;van Rooij and Videler, 1997;Choat et al, 2003;Paddack et al, 2009) which made it possible to model effectively. Our model extends the model of stoplight parrotfish created by Bozec et al (2016) by incorporating life phase and sex change explicitly.…”
Section: Research Articlementioning
confidence: 99%
“…Since the Caribbean region‐wide mass mortality of the urchin Diadema antillarum in 1983 (Lessios et al, ), parrotfish grazing alone may be insufficient to reduce macroalgal cover in areas of high fishery exploitation (Burkepile & Hay, ). Because of the increase in the harvesting of parrotfishes (Pavlowich & Kapuscinski, ), controls on the extraction of major grazers have been implemented in some countries in the region (Belize (Montero, ), Bonaire (Jackson et al, 2014) and the Turks and Caicos Islands (Mumby, ), but it has been recommended that an outright ban on parrotfish extraction be implemented throughout the Caribbean (Jackson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the increase in the harvesting of parrotfishes (Pavlowich & Kapuscinski, 2017), controls on the extraction of major grazers have been implemented in some countries in the region (Belize (Montero, 2009), Bonaire (Jackson et al, 2014) and the Turks and Caicos Islands (Mumby, 2016), but it has been recommended that an outright ban on parrotfish extraction be implemented throughout the Caribbean (Jackson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%